Real business cycle realizations - Gregor W. Smith; Stanley E. Zin (Queen's University, Department of Economics, 1997)
Much recent business cycle research focuses on moments of macroeconomic aggregates. We construct examples of real business cycle sample paths for output, consumption, and employment for the U.S. economy. Annual sample paths are generated from an initial condition in 1925, measured technology and government spending shocks since then, and a standard, calibrated, one-sector model of the business cycle. Quarterly sample paths are generated similarly, from an initial condition in 1955. The law of motion for shocks is not parametrized and so decision-rules are estimated by GMM. We compare the paths with actual history graphically and by spectral methods.
Keywords: E32; E27; 330; real business cycles; Solow residuals; US business cycle history